Motivations and challenges of home-based apparel live sellers - Garcia, Angelica Mae Ramos; Chua, Consuelo T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Live selling has emerged as a popular option for entrepreneurship due to its relatively easier market entry that is made accessible by digital technology. However, despite its growing prominence, research on live selling has focused more on consumer perspectives, overlooking the viewpoint of the entrepreneurs. Thus, this study explored the motivations and challenges of home-based apparel live sellers and examined the contribution of the business to individual and family income. Eleven live sellers were interviewed for the study. The results showed that passion and life goals and need for an additional source of income were the primary motivators that encouraged the live sellers to begin live selling. The most common challenges faced by live sellers include deceptive buyers, inconsistent supplies, the lack of space for inventory, and lack of time for their family. From these experiences, the live sellers have gradually learned to effectively cope with the challenges they encounter by implementing suitable solutions and strategies for each specific problem. The study emphasizes the importance of exploring the experiences of home-based live sellers to initiate further investigations on home-based businesses.
Thesis (Bachelor of Science in Home Economics) -- University of the Philippines Diliman
Bibliography: pages 56-60.
Keywords: Home-based businesses -- Philippines; Electronic commerce -- Philippines; Businesspeople -- Philippines